Effects of chronic kidney disease and declining renal function on coronary atherosclerotic plaque progression: a PARADIGM substudy. (12th March 2021) - Huang, Alex L.; Leipsic, Jonathon A.; Zekry, Sagit Ben; Sellers, Stephanie; Ahmadi, Amir A.; Blanke, Philipp; Hadamitzky, Martin; Kim, Yong-Jin; Conte, Edoardo; Andreini, Daniele; Pontone, Gianluca; Budoff, Matthew J.; et al.
Abstract: Aims : To investigate the change in atherosclerotic plaque volume in patients with chronic kidney disease (CKD) and declining renal function, using coronary computed tomography angiography (CCTA). Methods and results: In total, 891 participants with analysable serial CCTA and available glomerular filtration rate (GFR, derived using Cockcroft–Gault formulae) at baseline (CCTA 1) and follow-up (CCTA 2) were included. CKD was defined as GFR <60 mL/min/1.73 m 2 . Declining renal function was defined as ≥10% drop in GFR from the baseline. Quantitative assessment of plaque volume and composition were performed on both scans. There were 203 participants with CKD and 688 without CKD. CKD was associated with higher baseline total plaque volume, but similar plaque progression, measured by crude (57.5 ± 3.4 vs. 65.9 ± 7.7 mm 3 /year, P = 0.28) or annualized (17.3 ± 1.0 vs. 19.9 ± 2.0 mm 3 /year, P = 0.25) change in total plaque volume. There were 709 participants with stable GFR and 182 with declining GFR. Declining renal function was independently associated with plaque progression, with higher crude (54.1 ± 3.2 vs. 80.2 ± 9.0 mm 3 /year, P < 0.01) or annualized (16.4 ± 0.9 vs. 23.9 ± 2.6 mm 3 /year, P < 0.01) increase in total plaque volume. In CKD, plaque progression was driven by calcified plaques whereas in patients with declining renal function, it was driven by non-calcified plaques. Conclusion: Decline in renal function was associated with more rapid plaque progression, whereas the presence of CKD was not. Graphical Abstract: